Application of total productive maintenance (TPM) concept in palm oil [Elaeis guineensis] mill factory [Malaysia] - Muhamad Zameri Mat Saman (2013)
This study is about the application of total productive maintenance (TPM) concept in a palm oil mill factory. The objective of this paper is to highlight the advantage of TPM concept and to increase the operating efficiency of equipment recognized as the overall equipment efficiency (OEE) on shop floor. In consequence this should bring benefits to the particular factory. A case study was carried out in a palm oil mill factory to investigate existing situation. Pilot equipment was selected to serve as a target for TPM implementation in improvement prioritization analysis. In consequence, a list of all possible causes of losses was established and countermeasures to eliminate losses were recommended.